Effects of Adoption of Improved Sheabutter Processing Technology on Women’s Livelihoods and their Microenterprise Growth - Mohammed, Fadilah; Boateng, Seth; Al-hassan, Seidu (American Journal of Humanities and Social Sciences, 2013)
<!--[if gte mso 9]> <![endif]--> This paper investigates the effects of adoption of improved shea butter processing technology on women’s livelihood and microenterprise growth using 300 women enterprise owners. The sample was stratified into three groups: Full adopters (FA), Partial adopters (PA) and Non-adopters (NA). The study was undertaken in nine (9) communities drawn from the Tamale Metropolis and the Tolon/Kunbumgu District of the Northern Region of Ghana. The results reveal that full adopters have improved their income, savings, employment, investment and credit levels as a result of adopting improved method of processing shea butter. Results of t-test suggest a significant difference in income, savings, employment, investment and credit levels. Enterprises owned by women who adopted the improved technology have improved more than those who did not adopt. It is concluded that the adoption of improved technology has had positive effect on the livelihoods of women and enterprise growth. It is recommended among other things that shea butter processors, particularly non-adopters should be exposed to the improved shea butter processing technology and also be given training on their usage to enhance the growth of their enterprises. <!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE AR-SA <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]-->